Pengaruh Hedonisme, Pendapatan, dan Literasi Keuangan Terhadap Pengelolaan Keuangan dengan Self Control ebagai Moderasi - Uhti Noer Choliza Safitri; Hwihanus Hwihanus (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
The purpose of this research is to determine how income, lifestyle hedonism, and financial literacy impact the financial management of students at the University of August 17, 1945 Surabaya, with self-control as a moderating variable.This research uses a quantitative approach with a descriptive research type. Purposive sample of 30 active university students studied on August 17, 1945. The data analysis techniques used are Multiple Linear Regression and Moderation Regression, which were analyzed using the SPSS program. The research results show that financial literacy and a hedonistic lifestyle have a significant impact on students' financial management, while income does not have a significant impact. Overall, self-control does not strengthen the relationship between financial literacy, income, and a hedonistic lifestyle on their personal financial management.